Substituent-controlled construction of A4B2-hexaphyrins and A3B-porphyrins: a mechanistic evaluation - Cinar, Seda; Tasgin, Dilek Isik; Unaleroglu, Canan (Beilstein Journal of Organic Chemistry, 2023)
A substituent-dependent construction of novel A3B-porphyrins along with A4B2-hexaphyrins was realized by the reactions of N-tosylimines and meso-aryl-substituted tripyrranes in the presence of Cu(OTf)2 as the catalyst. The reaction mechanism of the presented method was studied on model reactions by electrospray-ionization time-of-flight (HRESI–TOF) mass spectral analysis in a timely manner. The analytical results indicated that the observed azafulvene-ended di- and tripyrrolic intermediates are responsible for the formation of porphyrinogen and hexaphyrinogen forms.
Keywords: A4B2-hexaphyrin; A3B-porphyrin; N-tosylimine; Cu(OTf)2 catalysis; HRESI–TOF analysis